2010
DOI: 10.1097/tp.0b013e3181f7fec9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cutoff Point for Immunoperoxidase Detection of C4d in the Renal Allograft: Results From a Multicenter Study

Abstract: Background Although C4d deposition in peritubular capillaries has been identified as a strong risk factor for subsequent renal allograft loss, the optimal cut-off for the fraction of peritubular capillaries needed to establish a positive stain in formalin-fixed paraffin-embedded material has not been systematically defined. The objective of this study was to establish the threshold for positive staining that best predicts renal outcome in renal biopsies in a multicenter study in which local and central patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Five companion reports were used for supplementary data. 9,10,[32][33][34] Figure 1 presents the flow diagram of search results. A total of 3485 indication and 868 surveillance biopsies were included.…”
Section: Resultsmentioning
confidence: 99%
“…Five companion reports were used for supplementary data. 9,10,[32][33][34] Figure 1 presents the flow diagram of search results. A total of 3485 indication and 868 surveillance biopsies were included.…”
Section: Resultsmentioning
confidence: 99%
“…However, the incidence of C4d-positive AMR in grafts varies depending on the proportion of sensitized patients, as has been shown in previous reports. [27][28][29][30][31] The reason for using C4d, the split product of complement component 4 (C4), as a marker for AMR is based on its role in the complement cascade. 1 There are three main pathways for complement activation: the classical, lectin, and alternative pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of C4d staining that accurately predicts kidney transplantation outcome is still debated, and even a cutoff of 10% for C4d positivity was reported to be a strong predictor of renal graft loss. 27 Several studies had compared IF and IHC on frozen and paraffin sections for C4d identification and grading in kidney graft biopsies. Some of them showed higher accuracy for frozen-IF with monoclonal antibody in relation to paraffin-IHC, 14,15,28 but other authors reported an acceptable sensitivity (87.5%) and specificity (98%) of paraffin-IHC with anti-C4d polyclonal antibody.…”
Section: Discussionmentioning
confidence: 99%